Impact of wind in the architectural shape of residential high buildings Goizha residential complex in Sulaymani city as a case study - Tayib, Abdullah; Mahmood, Fouad Jalal (Sulaimani Journal for Engineering Sciences, 2015)
The wind and its movement is one of the most significant environmental effects that should be taken into consideration in the preparation of the preliminary designs for any project. In spite of the large number of research and studies on the relationship between the building shape and the design vocabulary on the one hand, the wind movement and its flow of the other hand, they did not address in detail to determine the properties of architectural shape of high buildings compatible with wind speed and its direction. This paper attempts to find the relationship between the wind movement and architectural shape of high buildings in its both directions horizontally and vertically and the possibility to take advantage of the flow of air moving around it through controlling its flow for achieving climate balance which plays influential role in setting priorities in the design process. As the change in wind speed and its direction affect the composition of architectural shape of high buildings, as well as affect the efficiency of these buildings in achieving aerobic comfort in varying degrees. Goijha residential complex in Sulaymani city has been selected as a case study using the software program (ANSYS CFX12) in measuring the impact of wind on the architectural shape. The findings confirmed the validity of research hypothesis in existence of a relationship between the wind movement and architectural shape reflected in the emergence of a change in wind speed and its nature around the high buildings with a change in wind comfort factor as a result. The paper recommends using building layouts and directing the buildings to the east to the south-east due to its suitability with wind movement in the study area .
Keywords: Air movement; Wind; Architectural shape; High rise building